The rise of India's global health diplomacy amid COVID-19 pandemic - Vijay Kumar Chattu; Bawa Singh; Fnu Kajal; Chakrapani Chatla; Soosanna Kumary Chattu; Sanjay Pattanshetty; K. Srikanth Reddy (Tabriz University of Medical Sciences, 2023)
The COVID-19 pandemic has highlighted the importance of global health diplomacy (GHD), with India emerging as a key player. India's commitment to GHD is demonstrated by its active participation in regional and multilateral projects, pharmaceutical expertise, and large-scale manufacturing capabilities, which include the production and distribution of COVID-19 vaccines and essential medicines. India has supported nations in need through bilateral and multilateral platforms, providing vaccines to countries experiencing shortages and offering technical assistance and capacity-building programs to improve healthcare infrastructure and response capabilities. India's unique approach to GHD, rooted in humanitarian diplomacy, emphasized collaboration and empathy and stressed the well-being of humanity by embracing the philosophy of "Vasudhaiva Kutumbakam," which translates to "the world is one family." Against this background, this paper's main focus is to analyze the rise of India's GHD amidst the COVID-19 pandemic and its leadership in addressing various global challenges. India has demonstrated its commitment to global solidarity by offering medical supplies, equipment, and expertise to more than 100 countries. India's rising global leadership can be attributed to its proactive approach, humanitarian diplomacy, and significant contributions to global health initiatives.